2011
DOI: 10.1097/qad.0b013e328343489e
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quasispecies variants predicted to use CXCR4 by ultra-deep pyrosequencing during early HIV infection

Abstract: Our findings show that X4 variants may be frequently found, at variable intrapatient frequency, in early infected patients, and that quasispecies diversity and absolute numbers of X4 variants are significantly higher in patients undergoing early antiretroviral treatment. Further studies are mandatory to explore the clinical relevance of X4 variants present during early infection with respect to clinical progression and possible therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Early in the course of infection, most HIV isolates utilize CCR5 (56,74,86); however, several recent reports have demonstrated that CXCR4-utilizing viral subpopulations are found in as many as 10 to 50% of recently infected individuals (1,14). In addition, CXCR4-utilizing viruses emerge in many patients later in the course of infection (55,66).…”
Section: Cd45romentioning
confidence: 99%
“…Early in the course of infection, most HIV isolates utilize CCR5 (56,74,86); however, several recent reports have demonstrated that CXCR4-utilizing viral subpopulations are found in as many as 10 to 50% of recently infected individuals (1,14). In addition, CXCR4-utilizing viruses emerge in many patients later in the course of infection (55,66).…”
Section: Cd45romentioning
confidence: 99%
“…However, there is no detailed analysis of NDV quasispecies yet, and the relationship between emergent virulent strains and NDV quasispecies has not been clarified. Ultradeep pyrosequencing (UDPS) has emerged as an important tool with which to investigate viral diversity and to detect mutants in a group of quasispecies (24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…In the past, efforts have been made to use NGS-based approaches, in particular pyrosequencing, for obtaining genetic data from different viral pathogens, such as HIV; avian leukosis virus; lyssaviruses; enteric viruses, and few arboviruses, including DENV-1 and phleboviruses (Victoria et al, 2009;Bimber et al, 2010;Bishop-Lilly et al, 2010;Day et al, 2010;Hedskog et al, 2010;De Wolf et al, 2011;Schinazi et al, 2011;Abbate et al, 2011;De Benedictis et al, 2011;Palacios et al, 2011).…”
Section: Discussionmentioning
confidence: 99%